Proceedings of the Second International Scientific Conference "Intelligent Information Technologies for Industry" (IITI'17) Volume 2 - Abraham, Ajith; Kovalev, Sergey; Tarassov, Valery; Snasel, Vaclav; Vasileva, Margreta; Sukhanov, Andrey; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume of Advances in Intelligent Systems and Computing highlights key scientific achievements and innovations in all areas of automation, informatization, computer science, and artificial intelligence. It gathers papers presented at the IITI 2017, the Second International Conference on Intelligent Information Technologies for Industry, which was held in Varna, Bulgaria on September 14-16, 2017. The conference was jointly co-organized by Technical University of Varna (Bulgaria), Technical University of Sofia (Bulgaria), VSB Technical University of Ostrava (Czech Republic) and Rostov State Transport University (Russia).   The IITI 2017 brought together international researchers and industrial practitioners interested in the development and implementation of modern technologies for automation, informatization, computer science, artificial intelligence, transport and power electrical engineering. In addition to advancing both fundamental research and innovative applications, the conference is intended to establish a new dissemination platform and an international network of researchers in these fields. .
Approach to the search for similar software projects based on the UML ontology -- Method for conceptual presentation of subject tasks in knowledge engineering for computer-aided design systems -- Energy Meter for Smart Home Purposes -- Reconﬁgurable Distributed Information and Control System Multiagent Management Approach -- Intellectualization of Sorting Processes based on Instrumental Deﬁnition of Analogies -- Sensing thermal processes with Piezoelectric Film Elements -- Multithreaded hybrid library -- On the Electrodynamics of Moving Bodies According to the Rotary Theory -- Design and implementation of high speed AES on a RISC microcontroller -- Electronic Diﬀerentials with Active Torque Distribution for IWD Vehicles.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence